Is the Moderating Effect of Social Support on New Korean Mothers' Psychological Distress Contingent on Levels of Marital Quality?. (March 2018) - Park, Ki Tae
This study examines how levels of marital quality change the effect of social support on postpartum psychological distress among new Korean mothers using the Panel Study on Korean Children (N = 1585). In accord with findings from previous studies, this study shows that low marital quality negatively affects new mothers' mental health, but that social support alleviates psychological distress independent of marital quality. The main finding of this research is that the moderating effect of social support is contingent on levels of marital quality. Aggregated social support moderates the effects of marital quality on new mothers' mental health only when the level of marital quality is low. Furthermore, each dimension of social support (emotional, informational, and instrumental) only has a moderating effect when marital quality is low. The findings highlight the fact that the moderating effect of social support varies with the individual context and so customized social support that fits individual needs matters for the mental health of new mothers.